Duration of stretch does not influence the degree of force loss following static stretching - Brandenburg, J. P. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: There is an emerging body of knowledge indicating static stretching (SS) acutely and adversely affects muscle performance. The practical value of this research is limited considering the lengthy stretch durations under investigation. It is unclear if stretch durations typical of those used pre-exercise similarly affect muscle performance. The purpose of this study was to determine if SS using more representative stretch durations affects muscle performance and to establish if changes in muscle performance were influenced by the duration of stretch. Methods: Following 2 familiarization sessions, 16 recreationally trained males and females participated in 2 randomly ordered experimental sessions. In each session maximal effort hamstring performance was assessed prior to and immediately after 1 of 2 stretching protocols. During one of the protocols participants were required to hold each stretch for 15 s while stretch duration in the second protocol was 30 s. Both protocols consisted of 3 repetitions of 2 stretching exercises. A Kincom isokinetic dynamometer was used to assess hamstring performance during isometric, concentric, and eccentric actions. Results: For each of the three muscle actions a repeated measures ANOVA revealed a significant main effect of time (pre- vs poststretch, P<0.05) but no interaction effect (time x SS protocol). Furthermore, the stretch-induced deficits in muscle performance were consistent across muscle action type. Conclusions: SS incorporating stretch durations typical of those employed pre-exercise were sufficient to impair muscle performance and the duration of stretch did not influence the degree of force loss. Inclusion of SS, even with short stretch durations, in preparation for strength activities is not appropriate.